Cargo piers in dredging harbour waters - Kudzys, Antanas; Vaicekauskas, Laimutis J. (Transport, 2005)
Structural behaviour and reliability peculiarities of cargo piers in deepened harbour waters are discussed. Deterministic and probabilistic reliability assessment methods for permeable cargo piers exposed to lateral berthing actions and gravity permanent and variable loads are analysed. Some new methodological approaches to probabilistic reliability assessment of existing cargo piers are presented. The survival probability assessment of pier piles is based on their irreversible serviceability and safety margins. The numerical example illustrates the virtue of probability‐based approaches and methods of design practice of cargo piers. First Published Online: 27 Oct 2010